1994
DOI: 10.1111/j.1432-1033.1994.tb18800.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a two‐subunit cytochrome‐b‐containing heterodisulfide reductase from methanol‐grown Methanosarcina barkeri

Abstract: Heterodisulfide reductase catalyzes the terminal step in the energy-conserving electron-transport chain in methanogenic Archaea. The heterodisulfide reductase activity of the membrane fraction of methanol-grown Methanosarcina barkeri was solubilized by Chaps. Chromatography on Q-Sepharose and Superdex-200 yielded a high-molecular-mass fraction (> 700 kDa) which was dissociated by dodecyl P-D-maltoside. After chromatography on Q-Sepharose, an active heterodisulfide reductase preparation was obtained which was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…The same effect was described for membrane preparations of acetate-grown M s barkeri by Kemner et al (1987). Additionally, a membrane-bound multienzyme complex composed of a Fa,,-nonreactive hydrogenase, a cytochrome b, and the heterodisulfide reductase was isolated (Heiden et al, 1993(Heiden et al, , 1994 reported to accept electrons from reduced F4," (Kamlage and Blaut, 1992). Cytochrome reduction by H, was reported to be comparatively slow.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The same effect was described for membrane preparations of acetate-grown M s barkeri by Kemner et al (1987). Additionally, a membrane-bound multienzyme complex composed of a Fa,,-nonreactive hydrogenase, a cytochrome b, and the heterodisulfide reductase was isolated (Heiden et al, 1993(Heiden et al, , 1994 reported to accept electrons from reduced F4," (Kamlage and Blaut, 1992). Cytochrome reduction by H, was reported to be comparatively slow.…”
Section: Discussionmentioning
confidence: 80%
“…The 27-kDa cytochrome was subjected to N-terminal sequencing and the sequence MKSNNNPKAMVVERY was obtained. The N-terminus of the 25-kDa cytochrome was determined to be EMAYFSGLS-ALR(L)(G)FVQIM(I), which shows 95 % similarity to the cytochrome b subunit of the heterodisulfide reductase from Ms barkeri (Heiden et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…HdrC was shown to contain two binding motifs for [4Fe)4S] clusters while in subunit HdrB no characteristic binding motif of any known cofactor could be identified. However, this subunit contains 10 highly conserved cysteine residues present in two Cx 31)38 CCx 33)34 Cx 2 C motifs.The second type of Hdr, designated as HdrDE, is found in Methanosarcina species [4,6]. This enzyme is tightly membrane bound.…”
mentioning
confidence: 99%
“…The second type of Hdr, designated as HdrDE, is found in Methanosarcina species [4,6]. This enzyme is tightly membrane bound.…”
mentioning
confidence: 99%
See 1 more Smart Citation